2022
DOI: 10.2196/38454
|View full text |Cite
|
Sign up to set email alerts
|

State-of-the-Art Deep Learning Methods on Electrocardiogram Data: Systematic Review

Abstract: Background Electrocardiogram (ECG) is one of the most common noninvasive diagnostic tools that can provide useful information regarding a patient’s health status. Deep learning (DL) is an area of intense exploration that leads the way in most attempts to create powerful diagnostic models based on physiological signals. Objective This study aimed to provide a systematic review of DL methods applied to ECG data for various clinical applications. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 350 publications
(156 reference statements)
0
17
0
1
Order By: Relevance
“…In various papers, the state‐of‐the‐art study on deep learning has shown satisfactory results in detection, classification, and prediction tasks on medical images in general and ECG in particular. Several types of research have been done using different techniques to detect and automatically predict coronavirus contamination and other pathologies 44–47 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In various papers, the state‐of‐the‐art study on deep learning has shown satisfactory results in detection, classification, and prediction tasks on medical images in general and ECG in particular. Several types of research have been done using different techniques to detect and automatically predict coronavirus contamination and other pathologies 44–47 …”
Section: Discussionmentioning
confidence: 99%
“…Several types of research have been done using different techniques to detect and automatically predict coronavirus contamination and other pathologies. [44][45][46][47] Numerous studies tried to build deep learning models to find the most suitable one for COVID-19 detection and prediction. Indeed, Attallah 14 used the same database we worked on.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, CNN and their variants, such as U-Net, are the most common DL architectures for R-peak detection. Yet, many researchers stated that the best accuracy was achieved by combining different DL architectures, at a cost of increasing complexity [ 90 ]. Single ECG lead DL architectures already outperform classical algorithms, but few use multiple leads.…”
Section: Related Workmentioning
confidence: 99%
“…Recently, methods from the field of deep learning (DL) became popular for ECG-related tasks (Somani et al 2021, Petmezas et al 2022. For example, DL-based ECG classifications show promising results reaching accuracy similar to human experts (Hannun et al 2019, Ribeiro et al 2020, Reyna et al 2021.…”
Section: Related Workmentioning
confidence: 99%